Retrospective Analysis of Prognostic Factors and Pregnancy Outcomes in Patients with Moderate-to-Severe Intrauterine Adhesions Following Hysteroscopic Adhesiolysis and Modified Intrauterine Stent Intervention - Peng Q; Cao CX; Chen YN; Liu WC; Zhao RK; Jiang QJ; Zhou Q (Therapeutics and Clinical Risk Management, 2025)
Qiao Peng,1,2 Chao-xia Cao,3 Yi-nan Chen,4 Wei-chu Liu,5 Rui-kun Zhao,5 Quan-jia Jiang,6 Qin Zhou5 1Reproductive Medicine Center, Suining Central Hospital, Suining, Sichuan, 629000, People’s Republic of China; 2Prenatal Diagnosis Center, Suining Central Hospital, Suining, 629000, People’s Republic of China; 3Department of Gynecology, Women and Children’s Hospital of Chongqing Medical University (Chongqing Health Center for Women and Children), Chongqing, 401147, People’s Republic of China; 4Department of Mathematics, University College London, London, WC1E 6BT, UK; 5Department of Obstetrics and Gynecology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 6Department of Obstetrics and Gynecology, Chongqing Shapingba Maternity & Child Healthcare Hospital, Chongqing, 401331, People’s Republic of ChinaCorrespondence: Qin Zhou, Department of Obstetrics and Gynecology, The First Affiliated Hospital of Chongqing Medical University, No. 1 of Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Tel +8613101383367, Fax +86023-89011082, Email zhqinou@hospital.cqmu.edu.cnObjective: To assess the clinical prognosis and reproductive outcomes in individuals presenting with moderate-to-severe intrauterine adhesion (IUA) following the administration of hysteroscopic adhesiolysis (HA) in conjunction with modified intrauterine stents.Methods: A cohort comprising 156 individuals diagnosed with IUA (105 with moderate severity and 51 with severe severity) was enrolled. Subsequent to hysteroscopic intervention, all participants received intrauterine stent placement during the immediate postoperative phase. A comprehensive follow-up period of 2 years post-stent removal was instituted.Results: The occurrence of adhesion recurrence increased progressively, demonstrating a recurrence rate of 11.54% at hysteroscopic reevaluation administrated in 3 months after surgery and surging to 32.69% during the 2-year follow-up period. Comparative analysis indicated a statistically significant reduction in recurrence rates among patients with moderate IUA compared to severe IUA (P < 0.05). The median duration of stent placement was determined to be 4 months. Postoperatively, patients exhibited a cumulative pregnancy rate of 71.79%, with a live birth rate of 79.28%. Significantly, patients with moderate IUA exhibited a significantly elevated pregnancy rate in comparison to those with severe IUA (P = 0.004). Multifactorial logistic regression analysis revealed that the severity of IUA was an independent risk factor for recurrence risk. Furthermore, the severity of IUA and postoperative re-adhesion emerged as contributory factors to the infertility observed in these patients.Conclusion: The combination of HA with a modified intrauterine stent demonstrates efficacy in the treatment of IUA; however, outcomes remain suboptimal for cases characterized by severity. The prognostic assessment of patients and the suggested criteria for the removal of intrauterine stents, as delineated in the study, are considered both feasible and recommendable for clinical practice. Furthermore, conscientious and attentive management is imperative for the mitigation of adverse pregnancy such as early pregnancy loss in individuals afflicted with IUA during pregnancy.Keywords: hysteroscopic adhesiolysis, hysteroscopy, intrauterine adhesion, intrauterine stent, pregnancy outcome